Kegiatan Simpan Pinjam Khusus Perempuan di Kecamatan Semparuk, Sambas - - Hamdi; Hartrisari Hardjomidjojo; Amiruddin Saleh (Institut Pertanian Bogor, 2013)
Women's savings and loan (SPP) activity is Indonesian government effort to develop rural savings and loan’s potency, access facility to micro scale enterprise funding, needs fulfill for funding basic social, institutional strengthening of woman activity, support poor households alleviation and create the employment. The objectives of this study were, to identify existing problems, to analyze strengths, weakness, opportunities and threats (SWOT) in the savings and borrowing activities from SPP groups and to improve strategies in the Project Management Unit (UPK) of Semparuk sub-district Sambas regency. The primary data were collected to fund user by observation and interviewed techniques, and secondary data obtained from literature studied. Interviews were conducted to 50 respondents whose used credit for three consecutive years and four program actors. The data explained descriptively and assessment strategies analyzed using internal factor evaluation matrix, external factor evaluation matrix, internal-external (IE) matrix, SWOT matrix and quantitative strategic planning matrix. The results show that identified problems were: poor households’ economic empowerment had not done yet, group members’ savings fail to grow, credit disbursement process was relatively slow, program actors’ role fail to facilitate the groups particularly in members’ businesses development. Several alternative strategies that can be implemented by District Management Unit (UPK) are: improve the services, expanse the credit markets and marketing networking, maximize the program actors’ role, maintain the commitment to developing the SPP, increase the programs promotion, increase the assistance to SPP groups and diversification of deposit and loan products.